Long‐term safety and efficacy of levodopa‐carbidopa intestinal gel in advanced Parkinson's disease - Fernandez, Hubert H.; Boyd, James T.; Fung, Victor S. C.; Lew, Mark F.; Rodriguez, Ramon L.; Slevin, John T.; Standaert, David G.; Zadikoff, Cindy; Vanagunas, Arvydas D.; Chatamra, Krai; Eaton, Susan; Facheris, Maurizio F.; et al. (Movement disorders, 2018)
ABSTRACT Background: Levodopa‐carbidopa intestinal gel (designated as carbidopa‐levodopa enteral suspension in the United States) provides stable plasma levodopa concentrations and reduces motor fluctuations in advanced Parkinson's disease patients through continuous delivery of levodopa via percutaneous endoscopic gastrojejunostomy. We report long‐term safety and efficacy outcomes from an open‐label phase 3 treatment program. Methods: PD patients (n = 262) who completed a 12‐week double‐blind study and its 52‐week open‐label extension or a separate 54‐week open‐label study were enrolled in this ongoing phase 3 open‐label, multinational study (NCT00660673). Safety and efficacy assessments were collected every 6 months. Results: Mean total duration of exposure to levodopa‐carbidopa intestinal gel was 4.1 years (range, 1.2 to 6.9 years). The overall discontinuation rate was 34% (average annual discontinuation rate, 10%). Although most patients (94%) reported an adverse event, the rate of adverse events decreased over time; 53% experienced a serious adverse event. Of patients in this extension study, 54% required jejunal tube replacement during the study, and 37% required percutaneous endoscopic gastrostomy tube replacement. Most patients were on levodopa monotherapy. Patients maintained reductions in “off” time and increases in mean “on” time without dyskinesia from initial levodopa‐carbidopa intestinal gel infusion to he study end point (P < 0.001; n = 81). Activities of daily living and quality‐of‐life assessments demonstrated significant improvements that persisted through the study. Conclusions: This long‐term study demonstrates sustained and clinically meaningful benefits from levodopa‐carbidopa intestinal gel in advanced PD patients. Although adverse event rates decreased over time, vigilance is required for device‐related complications and adverse events. © 2018 International Parkinson and Movement Disorder Society